2011
DOI: 10.1063/1.3664314
|View full text |Cite
|
Sign up to set email alerts
|

Rotational spectra and properties of complexes B⋯ICF3 (B = Kr or CO) and a comparison of the efficacy of ICl and ICF3 as iodine donors in halogen bond formation

Abstract: The ground-state rotational spectra of two weakly bound complexes B···ICF(3) (B = Kr or CO) formed by trifluoroiodomethane have been observed in pulsed jets by using two types of Fourier-transform microwave spectroscopy (chirped-pulse and Fabry-Perot cavity). Both complexes exhibit symmetric-top type spectra, thus indicating that the Kr atom in Kr···ICF(3) and both the C and O atoms in OC···ICF(3) lie along the C(3) axis of ICF(3). The rotational constant B(0), the centrifugal distortion constants D(J) and D(J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 40 publications
3
30
0
Order By: Relevance
“…It was recently shown that the complexes formed between CF 3 I and each of NH 3 and N(CH 3 ) 3 respectively contain halogen bonds, IÁ Á ÁN, with linear CAIÁ Á ÁN arrangements of atoms [2]. The length of the halogen bond in (CH 3 ) 3 NÁ Á ÁICF 3 is very similar to that associated with NÁ Á ÁI halogen bonds in crystal structures.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…It was recently shown that the complexes formed between CF 3 I and each of NH 3 and N(CH 3 ) 3 respectively contain halogen bonds, IÁ Á ÁN, with linear CAIÁ Á ÁN arrangements of atoms [2]. The length of the halogen bond in (CH 3 ) 3 NÁ Á ÁICF 3 is very similar to that associated with NÁ Á ÁI halogen bonds in crystal structures.…”
Section: Introductionmentioning
confidence: 81%
“…In each case, the iodine atom acts as electron acceptor for the coordinating NH 3 or N(CH 3 ) 3 Lewis base. It was shown [1,3] that H 2 S, H 2 O and CO respectively form halogen bonds to the iodine atom of CF 3 I in H 2 SÁ Á ÁICF 3 , H 2 OÁ Á ÁICF 3 and OCÁ Á ÁICF 3 . There are striking similarities between the structures of the BÁ Á ÁICF 3 complexes described above and comparators from the BÁ Á ÁIACl series where halogen bonding interactions result in the angle, \(CAIÁ Á ÁB)=180, in every case.…”
Section: Spectroscopic Analysis Of C 2 H 4 á á áIcfmentioning
confidence: 99%
See 2 more Smart Citations
“…Before discussing the methodology used and the results obtained during the cryospectroscopic experiments, it is worth noting that, since the first experiments reported in 2009 [48], a variety of complexes strongly related to those studied in the cryosolutions have now also been investigated using traditional and chirped-pulsed microwave studies [49][50][51][52][53][54][55], and that additional information on complexes between more complex perfluoro alkyl iodides and pyridine has also been obtained using low-temperature IR and NMR experiments [56].…”
Section: Introductionmentioning
confidence: 99%